On the 80th anniversary of Professor M.I.Balabolkin - Lyudmila Viktorovna Nedosugova; Nina Alexandrovna Petunina; Lyubov' Valentinovna Trukhina; Milena Eduardovna Tel'nova; Zoya Ivanovna Levitskaya (Сахарный диабет, 2014)
We introduce the audience to the personal and professional life of M.I. Balabolkin ? a prominent Russian endocrinologist, scientist and a proliferous author. We highlight his contribution into the development of national endocrinology services, including the foundation of academic departments of endocrinology in 1977 (first in the nation) and in 1991 (in the Institute of Higher Professional Education, now part of the First Moscow Medical University). We also attempt to summarize professor Balabolkin?s educational and scientific heritage that encompasses studies on pathogenesis and clinical management of major endocrine disorders, as well as instruction of a multitude of successful clinicians and scientists.